2020
DOI: 10.1101/2020.05.28.20115741
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chloroquine, hydroxychloroquine, and COVID-19: systematic review and narrative synthesis of efficacy and safety: Systematic review of (hydroxy)chloroquine efficacy and safety

Abstract: Background: The COVID-19 pandemic has required clinicians to urgently identify new treatment options or the repurposing of existing drugs. Several drugs are now being repurposed with the aim of identifying if these drugs provide some level of disease resolution. Of particular interest are chloroquine (CQ) and hydroxychloroquine (HCQ), first developed as an antimalarial therapy. There is increasing concern with regards to the efficacy and safety of these agents. The aims of this review are to systematically ide… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 82 publications
1
12
0
Order By: Relevance
“…Of the reviews without meta-analysis, 4 concluded that there was evidence for higher risk of mortality in the HCQ group (40,43,51,52) and one review (53) reported evidence of lower mortality in the HCQ group. Two reviews reported evidence of higher mortality in the chloroquine group (40,46) (Supplementary Table S6).…”
Section: Fig 3 Results Of Meta-analyses -Hcq and All-cause Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Of the reviews without meta-analysis, 4 concluded that there was evidence for higher risk of mortality in the HCQ group (40,43,51,52) and one review (53) reported evidence of lower mortality in the HCQ group. Two reviews reported evidence of higher mortality in the chloroquine group (40,46) (Supplementary Table S6).…”
Section: Fig 3 Results Of Meta-analyses -Hcq and All-cause Mortalitymentioning
confidence: 99%
“…The remaining 6 reviews (37,40,43,50,51,53) which did a narrative synthesis did not find a difference in the risk of transfer to the ICU, intubation or need for mechanical ventilation ( Supplementary Table S6).…”
Section: Transfer To the Icu Intubation And Mechanical Ventilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, recent literature has suggested that chloroquine may be associated with significant adverse effects when used in high dosages in the management of hospitalised COVID-19 patients (Takla, preprint, 2020) 33 , as the dosages required to reach therapeutic concentrations may increase the risk of adverse outcomes in this patient population 30 . Until results on the safety of chloroquine for the treatment of COVID-19 from high-quality randomised clinical trials (RCT) have been appraised, no specific recommendations on the safety of chloroquine in the management of patients with SARS COV-2 can be made, but it is advised that clinicians should avoid its use in patients with risk factors for QT prolongation.…”
Section: Safety Profile Of Chloroquinementioning
confidence: 99%
“…Although numerous countries have incorporated the off-label use of these drugs in their treatment policies, data guiding the rational dosing of these drugs in COVID-19 are lacking. A systematic review found that at least 4 different treatment regimens have been used thus far in studies assessing the use of chloroquine in COVID-19, with total dosages ranging from 3 000 mg to 20 000 mg over the course of treatment (Takla, preprint, 2020) 33 . Pre-clinical evidence suggests that relatively high dosages may be required in order to reach therapeutic tissue concentrations quickly 53 .…”
Section: Clinical Evidence For Chloroquine and Hydroxychloroquine Usementioning
confidence: 99%